(untitled) (Training and Practice : Journal of Educational Sciences, 2014)
In terms of public education, integrated education and its practical application receive increasing attention. For teachers, music therapy may be a proper tool for educating children. Listening to certain pieces of music has a calming effect on people. While creating music and rhythm, non-verbal connections are formed between teacher and child, or child and child. In teacher training, teaching practice provides an opportunity to get engaged in this topic. Teachers’ educational and developmental work may be a useful tool in this progress. By using music, we do not only teach music. Special needs teacher trainees receive music therapy as an optional subject.